2013
DOI: 10.3758/s13423-013-0458-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of cross-modal associations in statistical learning

Abstract: Our environment is richly structured, with objects producing correlated information within and across sensory modalities. A prominent challenge faced by our perceptual system is to learn such regularities. Here, we examined statistical learning and addressed learners' ability to track transitional probabilities between elements in the auditory and visual modalities. Specifically, we investigated whether cross-modal information affects statistical learning within a single modality. Participants were familiarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 39 publications
4
43
2
Order By: Relevance
“…In a subsequent test stage, participants were more accurate in recognizing the complete audiovisual transition (1/A-2/B) than in recognizing transitions between auditory stimuli alone [1-2] or visual stimuli alone [A-B]. However, another study (Glicksohn & Cohen, 2013) conversely suggested that learning audiovisual associations is more demanding. Participants were presented with triplets of auditory [1-2-3], visual [A-B-C] or audiovisual [1/A-2/B-3/C] stimuli that formed fixed "words" presented sequentially amongst other such words.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…In a subsequent test stage, participants were more accurate in recognizing the complete audiovisual transition (1/A-2/B) than in recognizing transitions between auditory stimuli alone [1-2] or visual stimuli alone [A-B]. However, another study (Glicksohn & Cohen, 2013) conversely suggested that learning audiovisual associations is more demanding. Participants were presented with triplets of auditory [1-2-3], visual [A-B-C] or audiovisual [1/A-2/B-3/C] stimuli that formed fixed "words" presented sequentially amongst other such words.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…The theoretical challenges that offline measures implicate are presented in figure 1, which outlines the components of individual performance in the classical visual SL (VSL) task (e.g. [3,17,36,75,76]; see [77] for a related approach).…”
Section: (B) Structural Confoundsmentioning
confidence: 99%
“…By analyzing recordings from wearable directional microphones attached to the heads of the participants who normally moved in various environments, Parise et al were able to conclude that the sources of the high-pitched sounds, in fact, tend to be elevated in the natural environment and, therefore, mapping between pitch and spatial height is likely to be grounded in this statistical regularity. The statistical regularities hypothesis and multisensory statistical learning, in particular, have received a lot of attention in the literature (e.g., Glicksohn & Cohen, 2013;Mitchel & Weiss, 2011); however, in many cases, the statistical origin of cross-modal associations is difficult to prove due to the need for substantial environment sampling. The hypothesis, at least theoretically, was extended to explain more complex second-order correspondences.…”
mentioning
confidence: 99%